The Impact of Social Networks on French Learning Among UDS Students, Nyankpala Campus - Immorrow, Mohammed Abdul-Rashid; Salifu, Abdul Kadir; Iddrisu, Sulemana; Tunteiya, Sulemana Shakira (Roczniki Nauk Społecznych, 2025)
This study investigates the impact of social network usage on French language learning among undergraduate students at the University for Development Studies (UDS), Nyankpala Campus. It examines the extent of social media use for French learning, its influence on language skills, and challenges faced by learners. A mixed-methods approach with an explanatory sequential design was adopted. All 21 French-learning students constituted the quantitative sample through a census method, while 6 were purposively selected for qualitative interviews. Data were collected via structured questionnaires and semi-structured interviews. Quantitative data were analyzed with SPSS v22 using descriptive and inferential statistics, including correlation and regression; qualitative data underwent thematic analysis. Findings show that platforms such as WhatsApp, YouTube, and Facebook are widely used for French learning. The study concludes that social networks significantly enhance receptive and oral skills but require structured curricular integration for comprehensive language development.